Deteksi Gen E-Cadherin Pada Karsinoma Sel Skuamosa Rongga Mulut dari Sampel Blok Paraffin - Nabiel .; Pradipto Subiyantoro; Vita Nirmala A (Nexus Biomedika, 2013)
Background : Oral cavity cancer is the most cancer type often found across the globe. The treatment and the progonosis of this cancer have a very good chance to succeed but otherwise the spread of the cancer cell (metastasis) has a very high extent on them. There are numerous cases to be found in metastasis process. This research aimed to detect E-Cadherin gene in oral cavity squamous cell carcinoma from paraffin block samples. Methods : This research used a DNA product which resulted from DNA isolation of 14 parafin block samples. First, the products was amplified using PCR. Second, the PCR products were run in a gel electrophoresis to find out E-Cadherin gene on each sample. Results : Twelve samples that were diagnosed as squamous cell carcinoma and amplified by PCR as well as run in gel electrophoresis using 2% of agarose showed positive bands of E-Cadherin gene. Otherwise, the same samples run in gel electrophoresis using 3% of agarose showed no positive band of E-Cadherin gene. Summary : Twelve samples that were diagnosed as squamous cell carcinoma of oral cavity showed positive bands of E-Cadherin gene in 2% of agarose and no one positive band of E-Cadherin gene in 3% of agarose. Keywords : E-Cadherin gene, paraffin blocks, squamous cell carcinoma of oral cavity